Peran Moderasi Board Characteristics dan Foreign Ownership terhadap Hubungan Kinerja Keberlanjutan dan Nilai Perusahaan di Indonesia - Rizky Trinanda Akhbar; Dian Puspita Ramadhan (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to analyze the moderating roles of board characteristics and foreign ownership on the relationship between Environmental, Social, and Governance (ESG) performance and firm value in Indonesia. Specifically, this research examines three moderating variables: (1) the proportion of female directors, (2) CEO age, and (3) the proportion of foreign ownership. Utilizing data from 33 LQ45 companies between 2023 and 2024 (yielding 66 observations), the study employs Moderated Regression Analysis (MRA) with mean centering to mitigate potential multicollinearity issues. The empirical results indicate that only the presence of female directors significantly strengthens the positive relationship between ESG performance and firm value—as measured by Tobin's Q. Conversely, neither CEO age nor foreign ownership exhibits a statistically significant moderating effect. These findings provide empirical support for the Resource-Based View and Stakeholder Theory, positioning gender diversity on corporate boards as a strategic asset that enhances the credibility and effectiveness of ESG implementation. Furthermore, the insignificance of CEO age suggests that basic demographic characteristics may be insufficient to moderate the ESG-firm value nexus, while the lack of significance regarding foreign ownership implies that external pressure from global investors does not automatically translate into improved ESG-driven firm value within the Indonesian context. This research offers practical implications for firms to prioritize board diversity to maximize the returns on sustainability investments, and for regulators to reinforce policies promoting gender diversity within corporate governance structures. Finally, this study highlights the necessity of exploring additional moderating variables in future research.